The anionic biosurfactant rhamnolipid does not denature industrial enzymes - Madsen, Jens K.; Pihl, Rasmus; Møller, Anders H.; Madsen, Anne T.; Otzen, Daniel E.; Andersen, Kell K. (Frontiers in Microbiology, 2015)
Biosurfactants (BS) are surface-active molecules produced by microorganisms. Their combination of useful properties and sustainable production make them promising industrial alternatives to petrochemical and oleochemical surfactants. Here we compare the impact of the anionic BS rhamnolipid (RL) and the conventional/synthetic anionic surfactant sodium dodecyl sulfate (SDS) on the structure and stability of three different commercially used enzymes, namely the cellulase Carezyme® (CZ), the phospholipase Lecitase Ultra® (LT) and the α-amylase Stainzyme® (SZ). Our data reveal a fundamental difference in their mode of interaction. SDS shows great diversity of interaction towards the different enzymes. It efficiently unfolds both LT and CZ, but LT is unfolded by SDS through formation of SDS clusters on the protein well below the cmc, while CZ is only unfolded by bulk micelles and on average binds significantly less SDS than LT. SDS binds with even lower stoichiometry to SZ and leads to an increase in thermal stability. In contrast, RL does not affect the tertiary or secondary structure of any enzyme at room temperature, has little impact on thermal stability and only binds detectably (but at low stoichiometries) to SZ. Furthermore all enzymes maintain activity at both monomeric and micellar concentrations of RL. We conclude that RL, despite its anionic charge, is a surfactant that does not compromise the structural integrity of industrially relevant proteins. This makes RL a promising alternative to current synthetic anionic surfactants in a wide range of commercial applications.